2016
DOI: 10.1159/000453066
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Infections in the Central Nervous System and Respiratory Tract Show Distinct Features in Hospitalized Children

Abstract: Background/Aims: Coronavirus (CoV) infections induce respiratory tract illnesses and central nervous system (CNS) diseases. We aimed to explore the cytokine expression profiles in hospitalized children with CoV-CNS and CoV-respiratory tract infections. Methods: A total of 183 and 236 hospitalized children with acute encephalitis-like syndrome and respiratory tract infection, respectively, were screened for anti-CoV IgM antibodies. The expression profiles of multiple cytokines were determined in CoV-positive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
170
0
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(190 citation statements)
references
References 36 publications
3
170
0
17
Order By: Relevance
“…In human infections with highly virulent respiratory viruses-such as avian influenza H5N1, H7N9, Severe Acute Respiratory Syndrome (SARS) coronavirus, and Coronavirus Disease-19 (COVID-19)-immunopathogenesis caused by the overproduction of pro-inflammatory cytokines may play an essential role in disease progression and mortality [3]. Several recent studies have reported that COVID-19 caused the destruction of the pulmonary parenchyma, including interstitial inflammation and extensive consolidation, similarly to the previously reported coronavirus infection [4,5]. During coronavirus infection, it was observed that the lungs increased in weight, with a mild pleural effusion of clear serous fluid, named pulmonary edema, and extensive consolidation [6,7].…”
mentioning
confidence: 73%
“…In human infections with highly virulent respiratory viruses-such as avian influenza H5N1, H7N9, Severe Acute Respiratory Syndrome (SARS) coronavirus, and Coronavirus Disease-19 (COVID-19)-immunopathogenesis caused by the overproduction of pro-inflammatory cytokines may play an essential role in disease progression and mortality [3]. Several recent studies have reported that COVID-19 caused the destruction of the pulmonary parenchyma, including interstitial inflammation and extensive consolidation, similarly to the previously reported coronavirus infection [4,5]. During coronavirus infection, it was observed that the lungs increased in weight, with a mild pleural effusion of clear serous fluid, named pulmonary edema, and extensive consolidation [6,7].…”
mentioning
confidence: 73%
“…As other viruses listed herein, HCoV are neurotropic and potentially neurovirulent. Even though no clear cause and effect link has ever been made with the onset of human neurological diseases, their neuropathogenicity is being increasingly recognized in humans, as several recent reports associated cases of encephalitis [244], acute flaccid paralysis [271] and other neurological symptoms, including possible complications of HCoV infection such as Guillain-Barré syndrome or ADEM [249,[272][273][274][275][276][277][278][279]. The presence and persistence of HCoV in human brains was proposed to cause long-term sequelae related to the development or aggravation of chronic neurological diseases [245][246][247][248][280][281][282].…”
Section: Human Coronaviruses In the Cns: Possible Associated Neurologmentioning
confidence: 99%
“…CoVs have been associated with CNS diseases such as acute viral encephalopathy, acute disseminated encephalomyelitis, and multiple sclerosis and are increasingly recognized as presenting a neurologic crisis [3,52,53]. In one series of 183 children hospitalized with acute encephalitis, 12% were associated with coronavirus infection [54]. Such propensity of CoVs has been documented for several of the beta-CoVs, including SARS-CoV and MERS-CoV [46,48].…”
Section: Covid-19: Potential Factors Contributing To Icu Deliriummentioning
confidence: 99%